(untitled) (Archives of Pediatrics of Uruguay, 2020)
Spontaneous monochorionic trigemellar pregnancies have a very low incidence, and there is no cause that may explain them. The chorionicity will determine the perinatal result of this gestations, but the frequency of poor results is higher as the number of fetuses sharing the same placenta increases. We present a case of a spontaneous monochorionic trigemellar gestation whose follow-up was carried out in the Pereira Rossell Pediatric Center with an excellent perinatal result